Acute parkinsonism in patients with systemic lupus erythematosus: a case report and review of the literature. (2nd September 2022) - Wantaneeyawong, Chayasak; Kasitanon, Nuntana; Kumchana, Kullanit; Louthrenoo, Worawit
Abstract: Purpose of the study: Parkinsonism in patients with systemic lupus erythematosus (SLE) is rare. This study reported a case of parkinsonism in SLE and reviewed the clinical features and outcomes of parkinsonism in SLE patients. Methods: English language literature of parkinsonism in SLE patients was reviewed. Results: There were 28 patients (19 adults and 9 children) with SLE and parkinsonism. Twenty-three patients were female. Of 26 patients whose disease duration was available parkinsonism occurred at SLE diagnosis and after SLE diagnosis in 6 and 20 patients, respectively. Twenty-five patients had active SLE. Hematologic, mucocutaneous and musculoskeletal systems were the 3 most common organs involved in SLE during parkinsonism onset. Rigidity, bradykinesia and resting tremor were the 3 most common parkinsonian symptoms. Compared with adults, child cases had significantly more psychosis (4 in 9 vs. 1 in 19, p = .026), seizures or psychosis (6 in 9 vs. 2 in 19, p = .005) and mutism (6 in 9 vs. none, p < .001). Brain magnetic resonance imaging (MRI) was abnormal in 13 of 24 patients. Eight of nine patients had abnormal single-photon emission computed tomography (SPECT) and 5 and 3 showed hypoperfusion and hyperperfusion, respectively. The outcomes were resolution, partial response and persistent symptoms in 17, 7 and 4 patients, respectively. The outcome was no different whether or not dopamine therapy was included to corticosteroids and/or immunosuppressive drugs. Conclusions: Parkinsonism in SLE usually occurs during active SLE disease. Good response to corticosteroid and/or immunosuppressive drugs supports the immunologic mechanism in the pathogenesis.